2004
DOI: 10.1002/eji.200324815
|View full text |Cite
|
Sign up to set email alerts
|

Commensal Gram‐negative bacteria prime human dendritic cells for enhanced IL‐23 and IL‐27 expression and enhanced Th1 development

Abstract: Dendritic cells (DC) are the main orchestrators of specific immune responses. Depending on microbial information they encounter in peripheral tissues, they promote the development of Th1, Th2 or unpolarized Th cell responses. In this study we have investigated the immunomodulatory effect of non-pathogenic intestinal Gram-negative (Escherichia coli, Bacteroides vulgatus, Veillonella parvula, Pseudomonas aeruginosa) and Gram-positive (Bifidobacterium adolescentis, Enteroccocus faecalis, Lactobacillus plantarum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
116
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(127 citation statements)
references
References 45 publications
10
116
0
1
Order By: Relevance
“…The canonical pathway, involved in innate immunity, is activated by proinflammatory stimuli, including TNF-a, various interleukins, microbes, and virus-related ligands. 47 Based on its close structural similarity with the viral oncoprotein v-Rel, the link between the NF-kB pathway and cancer was first suspected in 1990. 48 In the past decade, an increasing number of studies have shown that many cancers have constitutively active NFkB, including lung, colon, pancreatic, and ovarian cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The canonical pathway, involved in innate immunity, is activated by proinflammatory stimuli, including TNF-a, various interleukins, microbes, and virus-related ligands. 47 Based on its close structural similarity with the viral oncoprotein v-Rel, the link between the NF-kB pathway and cancer was first suspected in 1990. 48 In the past decade, an increasing number of studies have shown that many cancers have constitutively active NFkB, including lung, colon, pancreatic, and ovarian cancers.…”
Section: Discussionmentioning
confidence: 99%
“…IL-23 is essential for chronic inflammatory diseases and may be responsible for multiorgan inflammation (23). Several studies involving different infection models demonstrate that IL-23 can be induced in response to bacterial stimuli in human monocytederived dendritic cells (24) and macrophages (25), and contribute to the development of septic shock (10). Although IL-23 acts as an innate defense mechanism, it might contribute to exacerbating the inflammatory reaction, while, at a later stage, it may exert complex action on different cell types of the immune reactivity (10) .…”
Section: Discussionmentioning
confidence: 99%
“…IL-23 is secreted by human DCs exposed to gram-negative bacteria [101]. As mentioned above, IL-23 promotes the development and expansion of activated CD4 + T cells that produce IL-17, IL-17F, IL-6 and TNF and are called Th17.…”
Section: Il-12 and Its Familymentioning
confidence: 99%